Investigation of growth indices and photosynthesis pigments of Coontail (Ceratophyllum demersum) in exposure to silver nanoparticles - Mohammad Behzadi Tayemeh; Mona Tabarok; Hamid Salari Joo; Tayebeh Nemati; Seyed Ali Johari (بوم‌شناسی آبزیان, 2019)
The aim of this study was to assess the influence of silver nanoparticles (AgNPs) on growth indices and photosynthesis pigments content of Ceratophyllum demersum. Toxicity testing was conducted at different concentration of AgNPs (0, 0.001, 0.005, 0.025, 0.05, 0.1, and 0.5 mg l-1) in half-strength Hoagland media, during a 14-day period. The results indicated that the growth indices of C. demersum significantly decreased with increasing AgNPs concentration. The chlorophyll a, b, and total chlorophyll of C. demersum exhibited bell-shaped concentration-response after exposure to different concentrations of AgNPs. The pigments content significantly increased and decreased at low and high concentrations of AgNPs, respectively. The results of this experiment, generally, demonstrated that the silver nanoparticles induced toxicity on growth indices and pigments content of C. demersum. Taken together, the silver nanoparticles releases could disrupt health state and aquatic life in water ecosystems and greater caution is needed in the management of wastes containing AgNPs.